THE INFLUENCE OF HEALTH EDUCATION ON BREAST SELF-EXAMINATION (BSE) KNOWLEDGE FOR EARLY DETECTION OF BREAST CANCER IN WOMEN OF REPRODUCTIVE AGE - Sri Sumarni (Poltekkes Kemenkes Semarang, 2025)
Breast cancer is one of the main causes of death in women throughout the world. A total of 2.3 million women were diagnosed with breast cancer and 670,000 deaths worldwide. Early detection is very important to increase the success of treatment, one of which is breast self-examination (BSE). However, there are still many suburban age women who lack knowledge about BSE. Therefore, this study aims to determine the effect of health education about BSE on increasing knowledge of early breast cancer detection in suburban-age women in the Garung Community Health Center working area. This study used a pre-experimental design with a one-group pretest-posttest design. The Â sample consisted of 5 women of childbearing age who were selected using the Accidental Sampling Technique. The research results showed that there was a significant increase in the level of knowledge of respondents after being given BSE health education. Before the intervention, only 20% of respondents had a good level of knowledge, while after the intervention, this figure increased to 100%. The Wilcoxon test shows a p value of 0.043 (<0.05), which indicates that there is a significant influence of health education on increasing respondents' knowledge. Health education about BSE has a positive effect on increasing knowledge of early detection of breast cancer in women of childbearing age.